PENGARUH BRAND AMBASSADOR DAN KUALITAS PELAYANAN MELALUI KEPUTUSAN PEMBELIAN TERHADAP LOYALITAS PELANGGAN PADA APLIKASI SHOPEE - Dewi Irana Sari; Hasyim Hasyim (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This study is a quantitative study that aims to determine the influence of Brand Ambassador and Service Quality through Purchase Decisions on Customer Loyalty on the Shopee Application. The data collection technique was carried out using a Likert-scale questionnaire distributed online on Google Forms. The sampling technique used purposive sampling with a sample of 100 respondents, namely consumers or market users. The analysis technique used is Path Analysis. Then the results obtained that Brand Ambassador and Service Quality have a positive effect on Purchase Decisions, Purchase Decisions have a positive effect on Customer Loyalty. However, Brand Ambassadors on Customer Loyalty through Purchase Decisions have a greater influence than the direct influence of Brand Ambassadors on Purchase Decisions. So that the Purchase Decision can be said to have succeeded in becoming an intervening variable between Brand Ambassadors and Loyalty. Service Quality on Customer Loyalty has a greater influence than through Purchase Decisions. This means that consumers will be loyal or not to the product not because of the purchase decision made but because of the quality of service and the expectations that make them feel so that it can lead to customer loyalty.